DETERMINAN STRUKTUR MODAL PADA SEKTOR KONSTRUKSI BANGUNAN YANG TERCATAT DI BURSA EFEK INDONESIA - Arifin Siagian (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2016)
This studyaims to analyze the factors that influence the capital structure. The independent variables to be examined are company size, asset structure, profitability, liquidity, company growth, business risk and dividend policy. The population in this study is building construction sector companies which listed in Indonesia Stock Exchange. The samples used are 8 building contruction sector companies which have complete financial report from 2009 to 2013 and engaged in contruction business without through its subsidiary (holding company). The model used in this research is the fixed effects approach. The results show that partially the factors that influence the capital structure are company size, asset structure, profitability and liquidity, whereas company growth, business risk and dividend policy do not influence the capital structure. This study results also show that simultaneously 90,99 percentage the capital structure is influenced by the company size, asset structure, profitability, liquidity, company growth, business risk and dividend policy influence, whereas 9,01 percentage capital structure is influenced by others variable outside research model.